Callorhinus ursinus St. George Island, Pribilof Islands, Alaska, USA. Photo: Oriol Alamany in Otariidae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
Callorhinus ursinus St. George Island, Pribilof Islands, Alaska, USA. Photo: Oriol Alamany Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Otariidae, pp. 34-101 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 34, DOI: 10.5281/zenodo.6604474